A Review of Problem Based Learning (PBL) Approach in Tertiary Engineering Education - Debnath, Sujan (Curtin University, 2011)
Problem-based learning (PBL) is an approach of learning in which the problems provide the background motivation and driving force for learning. In PBL, students are provided with problems without any significant pre-knowledge to work out the solutions. It is suggested that a problem-based learning approach produces better-motivated students, develops a deeper understanding of the given problem, promotes independent and concerted learning, improves critical thinking, develops excellent cognitive skills, enhance problem-solving, group working and communication skills. This paper presents a review of some case studies of problem based learning in tertiary engineering education. The authors discuss how PBL approach is utilised to make teaching and learning engineering units more effective at tertiary engineering education.